Antimicrobial activity, phytochemical and toxicity analyses of salam [Syzygium polyanthum (Wight) Walp.] leaf extract and its application in food - Ramli, Suzita (2018)
Food products can be subjected to contaminate by bacteria and fungi. The growth of this microorganisms in food products can cause foodborne illness. To overcome this problem, the prevention should be done at the early stage of food processing such as sanitizing. Commonly, chemicals sanitizer had been apply in food industry. However, application of this chemicals for long term was affected human health. Therefore, development of natural sanitizer derived from plant sources are gaining more attention nowadays. In this study, the antimicrobial activity of salam [Syzygium polyanthum (Wight) Walp.] leaves extract was evaluated against 17 types of pathogenic microorganisms including Escherichia coli O157:H7, Klebsiella pneumoniae, Listeria monocytogenes, Proteus mirabilis, Pseudomonas aeruginosa, Salmonella Typhimurium, Staphylococcus aureus, Vibrio cholerae, Vibrio parahaemolyticus, Aspergillus flavus, Aspergillus niger, Rhizopus oligosporus, Rhizopus oryzae, Candida albicans, Candida krusei, Candida glabrata and Candida parapsilosis in order to determine the ability of S. polyanthum as natural food sanitizer. The susceptibility test showed that all tested pathogenic bacteria were inhibited by S. polyanthum extract, with the range of inhibition zone between 6.67 to 9.67 mm. The extract could inhibit the growth of L. monocytogenes and S. aureus with MIC of 0.63 mg/mL, meanwhile MIC of the extract against others pathogens were 1.25 mg/mL. L. monocytogenes can be killed completely at MBC value of 0.63 mg/mL, S. aureus, S. Typhimurium, V. cholerae and V. parahaemolyticus were at 1.25 mg/mL, while the other strains were at MBC value of 2.5 mg/mL. Time-kill curve study showed that E. coli O157:H7, L. monocytogenes, P. aeruginosa, S. aureus, V. cholerae and V. parahaemolyticus can be killed by S. polyanthum extract at 4× MIC for 4 h, 4× MIC for 1 h, 4× MIC for 1 h, 4× MIC for 4 h, 4× MIC for 4 h, 4× MIC for 4 h, respectively. However, the population of K. pneumoniae, P. mirabilis and S. Typhimurium showed 3 Log reduction after treated at 4× MIC for 4 h. All filamentous fungi species showed 6.5 mm in inhibition zone, while 1.25 mg/mL and 5.0 mg/mL for their MIC and MFC, respectively. In qualitative analysis of inhibition germination conidia, all the tested fungi species showed no growth after treated with extract started at 1× MIC for 9 days. Based on quantitative analysis, using 4× MIC for 24 h, the percentage of conidia germination were fully inhibited for A. flavus and R. oryzae (0%), meanwhile, for R. oligosporus and A. niger were reduced to 1% and 13%, respectively. Inhibition zone for Candida species were between 7.00-7.67 mm. For MIC and MBC, all Candida species can both inhibited and killed completely at range 0.63-1.25 mg/mL. C. albicans, C. glabrata and C. parapsilosis can be killed by S. polyanthum extract at 4× MIC for 4 h, 4× MIC for 2 h, 4× MIC for 4 h or 2× MIC for 4 h while the population of C. krusei reduced about 3 Log reduction after treated for 4× MIC for 4 h. Cell constituents release analysis and observation by using scanning electron microscope showed altering in cell wall linearity, cells ruptured and leakaged of the cytoplasm. Generally, the antimicrobial activities of S. polyanthum extract were not affected by different pH and temperatures. GC-MS analysis identified the presence of active compounds which responsible to contribute antimicrobial properties in S. polyanthum extract included pyrogallol, phytol, hexadecanoic acid, α-Tocopherol and β-Sitosterol while gallic acid, bergenin, quercetin 3-(6''- galloylgalactoside), madecassic acid, quillaic acid and asiatic acid were detected by using LC-MS. The toxicity study by using brine shrimp assay demonstrated that S. polyanthum, extract was not toxic to Artemia salina with LC50 was 75.85 mg/mL. Generally the significant reduction of natural microflora in tested food samples were started at 0.50% (v/v) of extract at 5 min. During storage, 5% (v/v) showed better effect in controlling the microbial survival throughout the storage time. Physical characteristics in term of colour, texture and odour, all the treated samples until the highest concentration of extract [5% (v/v)] showed not significantly different and this finding also parallel to sensory acceptability where 5% of extract was accepted by the panelists. In conclusion, S. polyanthum extract exhibited antimicrobial activity, thus it can be developed as natural sanitizer for washing raw food materials and prevent the food spoilage during storage.